WASTE COOKING OIL GASIFICATION WITH PRESSURE STOVES - Tamrin . (The University of Lampung, 2013)
Kerosene gasification with pressure stoves have been applied to people such mawar stoves. use of waste cooking oil as fuel for pressure stoves are still in the early stages of research. Waste cooking oil viscosity higher than that of kerosene, this is a problem in the use of the mawar stove, since mawar stove used of oil pipeline smaller than 2.5 mm. The research was carried out by utilizing the mawar stove by using waste cooking oil fuel. The results showed that the flow rate of kerosene from 2.33 to 4.08 ml/s on stove and flow rate of waste cooking oil on the stove from 0.39 to 0.66 ml/s with a pressure stove 6-3 psia. Waste cooking oil can be used as fuel for mawar stoves with pressure more than 4 psia and fire to preheat stove for waste cooking oil is greater than with the use of kerosene fuel. Keywords: Gasification, Kerosene Oil, Waste Cooking Oil, Mawar Stove And Pressure Stove